Noun class 9/10 tone in Central Ring Grassfields Bantu: An overview - (:unkn) unknown (My University, 2019)
Singular and plural noun roots in Grassfields Bantu languages may have different phonological shapes, be them segmental, tonal or both (e.g. Bafut (Tamanji 2009: 33), Bamoun (Watters 2003: 243, Mmen (Kiessling 2010: 10-13)). However, it becomes fascinating when such a variation proves to be complex and difficult to describe. Central Ring Grassfields languages (CRGL) of Northwest Cameroon are subject to a variety of complex tonal changes and present an intricate relationship particularly between the tones of the singular nouns (class 9) on the one hand and those of the plural (class 10) on the other. In this study, I attempt a unified analysis of the tonal intricacies within Autosegmental Phonology using data collected directly from native speakers and from existing literature. The study provides support for the claim that floating tones are central to the analysis of Grassfields Bantu languages (Hyman & Tadadjeu 1976).
Keywords: African Research